2014
DOI: 10.3748/wjg.v20.i29.10158
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effects of amifostine, ascorbic acid and N-acetylcysteine against methotrexate-induced hepatotoxicity in rats

Abstract: MTX-induced structural and functional damage to hepatic tissues in rats may involve oxidative stress, and cytoprotective agents (NAC > AMF > ASC) may alleviate MTX hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 22 publications
12
53
1
Order By: Relevance
“…It may be because of the single dose of MTX along with early sample collection. The findings are consistent with the Akbulut et al 13 and Tag 8 who also demonstrated elevation of LFTs in experimental rodents treated with MTX in same dose and route of administration. The exact pathogenesis of MTX induced hepatotoxicity is still unclear though different mechanisms are thought to participate in causing liver damage like accumulation of polyglutamates in hepatocytes, depletion of hepatic folate store resulting in decrease nucleic acid synthesis, inhibition of methionine biosynthesis and resultant increased homocysteine leading to increase cellular sensitization to reactive oxygen species (ROS) and reactive nitrogen species (RNS) along with lipid peroxidation of biological membranes and microvascular derangement.…”
supporting
confidence: 82%
“…It may be because of the single dose of MTX along with early sample collection. The findings are consistent with the Akbulut et al 13 and Tag 8 who also demonstrated elevation of LFTs in experimental rodents treated with MTX in same dose and route of administration. The exact pathogenesis of MTX induced hepatotoxicity is still unclear though different mechanisms are thought to participate in causing liver damage like accumulation of polyglutamates in hepatocytes, depletion of hepatic folate store resulting in decrease nucleic acid synthesis, inhibition of methionine biosynthesis and resultant increased homocysteine leading to increase cellular sensitization to reactive oxygen species (ROS) and reactive nitrogen species (RNS) along with lipid peroxidation of biological membranes and microvascular derangement.…”
supporting
confidence: 82%
“…Lyc, a powerful anti-oxidant, has been showed to be effective in reducing the nephrotoxicity caused by cisplatin, via decreasing oxidative stress (4,(38)(39)(40). Lyc's also has anti-infl ammatory and anti-cancer properties.The studies showed that it may be effective in reducing organ toxicity such as pancreas, testis and kidney (39,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several anti-oxidant agents have been used to reduce its side effects (10). Akbulut et al demonstrated the cytoprotective effects of amifostine, ascorbic acid and N-acetylcysteine against Mtx-induced hepatotoxicity in rats (4). In addition, it has been reported that proinfl ammatory cytokines are involved in the pathogenesis of Mtx-induced nephrotoxicity and pneumonitis, suggesting that infl ammation may also have a possible role in Mtx-induced hepatotoxicity (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals in the experimental groups were administered an intraperitoneal daily dose of a specific substance, depending on the group, and the control group received the same quantity of 0.9% sodium chloride solution daily (35) according to the following protocol: a) control group (0.9% sodium chloride 0.1-0.2 ml/day) (n=10); b) methionine (0.8 mmol/kg/bw/day) (n=10) (MET group); c) methionine (0.8 mmol/kg/bw/day) + L-cysteine (7 mg/kg/bw/day) (n=8) (L-cys+MET group) (36); and d) methionine (0.8 mmol/ kg/bw/day) + N-acetyl-L-cysteine (50 mg/kg/bw/day) (n=8) (NAC+MET group) (37). Prior to and during the research, all animals were permanently monitored, with tracking of the body weight of each animal in each group.…”
Section: Experimental Protocolmentioning
confidence: 99%